Jet Injection of Naked mRNA Encoding the RBD of the SARS-CoV-2 Spike Protein Induces a High Level of a Specific Immune Response in Mice - Denis N. Kisakov; Larisa I. Karpenko; Lyubov A. Kisakova; Sergey V. Sharabrin; Mariya B. Borgoyakova; Ekaterina V. Starostina; Oleg S. Taranov; Elena K. Ivleva; Oleg V. Pyankov; Anna V. Zaykovskaya; Elena V. Dmitrienko; Vladimir A. Yakovlev; et al. (Vaccines)
Background: Although mRNA vaccines encapsulated in lipid nanoparticles (LNPs) have demonstrated a safety profile with minimal serious adverse events in clinical trials, there is opportunity to further reduce mRNA reactogenicity. The development of naked mRNA vaccines could improve vaccine tolerability. Naked nucleic acid delivery using the jet injection method may be a solution. Methods: In the first part of the study, the optimal conditions providing low traumatization and high expression of the model mRNA-GFP molecule in the tissues of laboratory animals were determined. Then, we used the selected protocol to immunize BALB/c mice with mRNA-RBD encoding the SARS-CoV-2 receptor-binding domain (RBD). It was demonstrated that mice vaccinated with naked mRNA-RBD developed a high level of specific antibodies with virus-neutralizing activity. The vaccine also induced a strong RBD-specific T-cell response and reduced the viral load in the lungs of the animals after infection with the SARS-CoV-2 virus. The level of immune response in mice immunized with mRNA-RBD using a spring-loaded jet injector was comparable to that in animals immunized with mRNA-RBD encapsulated in LNPs. Results: In this study, the efficacy of an inexpensive, simple, and safe method of mRNA delivery using a spring-loaded jet injector was evaluated and validated. Conclusions: Our findings suggest that the jet injection method may be a possible alternative to LNPs for delivering mRNA vaccines against SARS-CoV-2 infection.